Seasonal variability of particulate organic carbon (POC) in a large asian tropical river: the red river (China/Vietnam) - Thi Ha, Dang; Coynel, Alexandra; Etcheber, Henri; Orange, Didier; Ngoc Anh Tu, Pham (Vietnam Journal of Science and Technology, 2017)
The Red River (China/Vietnam) is one of the largest Asian tropical rivers. Based on daily water discharge and suspended particulate matter (SPM) concentrations during the 2006 - 2009 period combining with the particulate organic carbon (POC) analyse at a permanent observation station (SonTay, near Hanoi), the seasonal variability of POC concentration was determined. The results showed that the % POC is generally quite low, varied between 0.62 % and 3.92 % with a mean of 1.44 %. In addition, a relation log – log exponential decrease between the SPM concentrations and POC contents (%) was observed, suggesting the dilution of both allochthonous (plants and woody materials) and autochthonous (riverine plankton) organic matter by mineral and clay materials from rock and soil erosion in the drainage area. In contrast, the POC concentration of the Red River at SonTay showed a similar evolution with the SPM concentrations. In fact, during the dry season, the monthly POC concentrations were low (0.91 ÷ 1.25 mg/l) and increased during the rainy season (1.71 ÷ 6.24 mg/l). Finally, we quantified the annual POC flux exported by the Red River into the Delta to be 154 × 103 ÷ 332 × 103 t/yr with the mean annual of 243 × 103 t/yr.